Public health in India : an overview - Das Gupta, Monica, 1975- 1975- (Policy research working paper, 2005)
"Public health services, which reduce a population's exposure to disease through such measures as sanitation and vector control, are an essential part of a country's development infrastructure. In the industrial world and East Asia, systematic public health efforts raised labor productivity and life expectancies well before modern curative technologies became widely available, and helped set the stage for rapid economic growth and poverty reduction. The enormous business and other costs of the breakdown of these services are illustrated by the current global epidemic of avian flu, emanating from poor poultry-keeping practices in a few Chinese villages. For various reasons, mostly of political economy, public funds for health services in India have been focused largely on medical services, and public health services have been neglected. This is reflected in a virtual absence of modern public health regulations and of systematic planning and delivery of public health services. Various organizational issues also militate against the rational deployment of personnel and funds for disease control. There is strong capacity for dealing with outbreaks when they occur, but not to prevent them from occurring. Impressive capacity also exists for conducting intensive campaigns, but not for sustaining these gains on a continuing basis after the campaign. This is illustrated by the near eradication of malaria through highly organized efforts in the 1950s, and its resurgence when attention shifted to other priorities such as family planning. This paper reviews the fundamental obstacles to effective disease control in India and indicates new policy thrusts that can help overcome these obstacles. "--World Bank web site